Environmental gaseous sensing using sniffer drone for urban development control. - Hj. Mohd. Noor, Norzailawati; Mazlan, Hashim (2021)
This study aims to present an environmental gaseous sensing analysis using drones in urban development control for the industrial area. The data collection method based on the possibility of gas dispersion in a heavy industrial area in Klang, Malaysia, to the neighbouring land uses. The sniffer has carried five types of gaseous sensors and mounted in DJI Matrice 100 quadcopter UAV. However, for this study, we analysed two significant gases related to an industrial area consisting of Carbon dioxide (CO2) and Hydrocarbon (CxH y). The information has been collect-ed in two modes of time which is in the early morning and afternoon. The data was mapped and analysed with a vector layer to identify either it breaches a concentration limits for gases collected. The finding stated that, the morning concentration reading is more dense compare to the after-noon. Results show that CO2 and CxHy still under control and minimise the risk for the local population. However, the safety precaution should be undertaken since gas dispersion's future potential would go beyond and affect the surrounding activities. In conclusion, this study shows the UAVs potential as one of the best mechanisms to monitor the environmental effect. Simultaneously, there is a need to review existing urban development control since climate change and sustainability are linked through their interaction in industries, and its surrounding land uses.